Electrospun Scaffolds of Polylactic Acid, Collagen, and Amorphous Calcium Phosphate for Bone Repair - William Cárdenas-Aguazaco; Bernardo Camacho; Edwin Yesid Gómez-Pachón; Adriana Lorena Lara-Bertrand; Ingrid Silva-Cote (MDPI AG, 2023)
Most electrospun scaffolds for bone tissue engineering typically use hydroxyapatite (HA) or beta tricalcium phosphate (β-TCP). However, the biological activity of these crystalline compounds can be limited due to their low solubility. Therefore, amorphous calcium phosphate (ACP) may be an alternative in bone repair scaffolds. This study analyzes the morphology, porosity, mechanical strength, and surface chemistry of electrospun scaffolds composed of polylactic acid and collagen integrated with hydroxyapatite (MHAP) or amorphous calcium phosphate (MACP). In addition, the in vitro biocompatibility, osteogenic differentiation, and growth factor production associated with bone repair using human Wharton's jelly-derived mesenchymal stem cells (hWJ-MSCs) are evaluated. The results show that the electrospun MHAP and MACP scaffolds exhibit a fibrous morphology with interconnected pores. Both scaffolds exhibit favorable biocompatibility and stimulate the proliferation and osteogenesis of hWJ-MSCs. However, cell adhesion and osteocalcin production are greater in the MACP scaffold compared to the MHAP scaffold. In addition, the MACP scaffold shows significant production of bone-repair-related growth factors such as transforming growth factor-beta 1 (TGF-β1), providing a solid basis for its use in bone tissue engineering.